People’s Influence on Indoor Body Area Networks Channel Characteristics - Slawomir J. Ambroziak; Filipe D. Cardoso; Manuel M. Ferreira; Mariella Sarestoniemi; Luis M. Correia (IEEE Access, 2024)
The influence of people’s presence on wideband off-body channel characteristics is presented in this paper. This research is significant for the development of Body Area Networks, as a promising solution for 5G and 6G networks, namely as an emerging technology expected to revolutionize mobile healthcare via real-time monitoring and analysis of medical data. The analysis is based on power delay profile measurements performed in an indoor office environment at 5.8 GHz (with a 500 MHz bandwidth), in which a single user walks along the room’s axis, for both the empty room and for six additional people inside it, which where static (i.e., preserving fixed posture and position), moving (i.e., changing postures at fixed positions) and walking (i.e., walking across the room). Models for the average system loss and the average delay spread are proposed, both for Line-of-Sight and Non-Line-of-Sight. The system loss exponent for Line-of-Sight is 0.8 and 1.8 for vertical and horizontal polarizations (of the transmitting antenna), respectively, while for Non-Line-of-Sight it is 1.2, regardless of polarization direction. The delay spread in the Line-of-Sight case is higher for the vertical polarization, being even higher when Non-Line-of-Sight is considered, regardless of polarization, reaching 12.2 ns. A strong correlation between delay spread and system loss is observed for Line-of-Sight. The general conclusion is that, for the investigated environment and scenarios, transmitting antenna’s polarization has a very significant impact on radio channel characteristics, including the polarization of the receiving antenna and the presence of other people in the room, which are less importance.